Photodegradation of rhodamine B over natural zeolite/ZnO - Utomo, M. Pranjoto; Prodjosantoso, Anti Kolonial; Budiasih, Kun Sri; Yunita, Isti; Triani, Tisia Miftakhul; Rahmawati, Vera Dwi Nur (Universitas Negeri Yogyakarta, 2024)
Rhodamine B is dye compound commonly used in the textile industry that consisted of azo compound. Azo compound generally difficult to be degraded. Undegradated azo compound in rhodamine B make it danger for the environment. An effective effort to handle rhodamine B waste must be conducted. Natural zeolite/ZnO is a material that can be used to degrade rhodamine B to be simpler compound based on photodegradation procces. Based on the analysis, the particle size of natural zeolite/ZnO is 16.92709 nm and the band gap energy 2.92 eV. The highest degradation percentage of rhodamine B over natural zeolite/ZnO under UV irradiation is 99.54%.